1990
DOI: 10.1111/j.1365-2788.1990.tb01520.x
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 13 (Patau's syndrome): a rare case of survival into adulthood

Abstract: ABSTRACT. Survival of cases of trisomy 13 (Patau's syndrome) into adulthood is a rare phenomenon. The purpose of this paper is to report one such survivor who has had the typical clinical features of trisomy 13 confirmed by chromosome analysis of both blood and skin, and to speculate on some of the factors that may have contributed to his unusually long survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…This may be due to the advanced management in the correction of cleft lip/palate in this hospital, and the prenatal recognition of cleft lip/palate is not a strong indicator for amniocentesis. Data on patients with mosaic trisomy 13 suggested that the relatively mild clinical manifestations in these patients were attributable to the presence of a normal cell line [Cowen et al, 1979; Singh, 1990; Zoll et al, 1993]. We suggest that non‐fatal congenital anomalies and aggressive medical care have played an important role in the prolonged survival of patients with trisomy 13 based on above findings [Zoll et al, 1993; Tunca et al, 2001; Duarte et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the advanced management in the correction of cleft lip/palate in this hospital, and the prenatal recognition of cleft lip/palate is not a strong indicator for amniocentesis. Data on patients with mosaic trisomy 13 suggested that the relatively mild clinical manifestations in these patients were attributable to the presence of a normal cell line [Cowen et al, 1979; Singh, 1990; Zoll et al, 1993]. We suggest that non‐fatal congenital anomalies and aggressive medical care have played an important role in the prolonged survival of patients with trisomy 13 based on above findings [Zoll et al, 1993; Tunca et al, 2001; Duarte et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that individuals with translocations or mosaic trisomy 13 have better survival rates, while other studies do not show any differences across these subgroups [Magenis et al, 1968; Hodes et al, 1978a,b; Rasmussen et al, 2003]. Although the prognosis for individuals with trisomy 13 is extremely poor, there have been six reports in the literature of individuals with trisomy 13 who have survived beyond 10 years of age [Redheendran et al, 1981; Singh, 1990; Zoll et al, 1993; Tunca et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…In another study of 70 infants, median survival was 7 days and only approximately 10% lived past 12 months of age [Rasmussen et al, 2003]. These and other site‐specific or population‐based investigations [Goldstein and Nielsen, 1988; Nembhard et al, 2001; Brewer et al, 2002; Cleves et al, 2003; Forrester and Merz, 2003; Crider et al, 2008; Vendola et al, 2010; Irving et al, 2011] describe brief life spans while case studies generally offer more positive outcomes [e.g., Singh, 1990; Zoll et al, 1993; Sweeney and Pelegano, 2000; Tunca et al, 2001; Iliopoulos et al, 2006]. In a sample of 11, Hsu and Hou [2007] found median survival was 95 days including a 7‐year‐old.…”
Section: Introductionmentioning
confidence: 99%